Nutritional status and food consumption of health residents of a public institution of Maceió-AL - Ferreira Do Espirito Santo, Nayara; Amorim Dos Santos, Ewerton; Merten Padilha, Bruna; Ferreira Do Espirito Santo, Mariane (O Mundo da Saúde, 2018)
The objective of this study was to characterize the food consumption and nutritional status of health residents of a public institution in Maceió-AL and to evaluate their association. This is a cross-sectional study carried out in the period from august to December 2016, with 58 health professionals, aged between 23 and 41 years, of both sexes, enrolled in the Multiprofessional Health Residency program of the Alagoas State University of Health Sciences, between 2014 and 2016. Socioeconomic, demographic, anthropometric, lifestyle, food consumption and antecedent clinical data were collected. Statistical analysis was performed using the SPSS 21.0. There were no overweight and no risk associated with metabolic changes. Adequate eating habits were identified with a varied diet. Overweight individuals had lower butter ingestion and higher use of sweetener (p<0.05). Eating habits are influenced by several factors, including the fact that they are health professionals. It is necessary to approach educational strategies about healthy eating among overweight individuals in order to stimulate them to achieve adequate weight.